2016
DOI: 10.1007/s10461-016-1655-8
|View full text |Cite
|
Sign up to set email alerts
|

The Where and How for Reaching Transgender Women and Men Who Have Sex with Men with HIV Prevention Services in Guatemala

Abstract: This study aims to describe the transgender women and men who have sex with men (MSM) missed through venue-based sampling and illustrate how data on venues can be used to prioritize service delivery. Respondent-driven sampling (RDS) and time-location sampling (TLS) were used concurrently in 2010 for behavioral surveillance among MSM and transgender women in Guatemala City. RDS recruits who did not frequent venues (n = 106) were compared to TLS recruits (n = 609). TLS participants recruited at different types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…While this finding may in part be explained by MSM inviting casual partners with whom they are more acquainted into their homes, it also highlights the danger of the perceived safety of repeat casual partners. In addition to further highlighting the potential risk of infectious disease transmission in environments perceived as “safe,” this finding also provides a more detailed understanding of the role of the site of sexual contact than previous studies of CAI and place in Latin America, which limited their analyses to commercial and/or public sex venues [12, 40]. Successful combination HIV and STI prevention interventions therefore cannot focus only on traditionally high-risk sex venues like saunas and public spaces, but must also offer MSM strategies to understand risks associated with established partners and to increase condom use in their own homes.…”
Section: Discussionmentioning
confidence: 93%
“…While this finding may in part be explained by MSM inviting casual partners with whom they are more acquainted into their homes, it also highlights the danger of the perceived safety of repeat casual partners. In addition to further highlighting the potential risk of infectious disease transmission in environments perceived as “safe,” this finding also provides a more detailed understanding of the role of the site of sexual contact than previous studies of CAI and place in Latin America, which limited their analyses to commercial and/or public sex venues [12, 40]. Successful combination HIV and STI prevention interventions therefore cannot focus only on traditionally high-risk sex venues like saunas and public spaces, but must also offer MSM strategies to understand risks associated with established partners and to increase condom use in their own homes.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of epidemiologic analyses of transgender populations have been based on convenience samples of individuals recruited from community, clinic, or commercial sex venues [11] . Although these studies provide important information on local population characteristics and identify specific areas for intervention, they may not accurately represent the epidemiologic characteristics of the larger transgender population.…”
Section: Sampling Methodologiesmentioning
confidence: 99%
“…29 Rather, the Center for Disease Control recounted an experience where they attempted to recruit transgender women through exploring their residences, social networks and other social spheres as well as common social spheres. 30 Transgender women in Bangladesh, indicated that they felt more comfortable visiting a community-based healthcare facility, particularly if they did not disclose their sexual orientation and if the facilities were catered to sexual minority populations. 17 …”
Section: Introductionmentioning
confidence: 99%
“…5 An estimated 1.2 million (range, 1.1-1.3 million) deaths due to TB disease occurs across the globe in 2018, in addition to 251 000 (range, 223 000-281 000) TB deaths happened among PLHIV. 5 This is because PLHIV are 29 (26)(27)(28)(29)(30)(31) times more vulnerable to TB than HIV negative individual. 6 In this context, TB is considered as the leading preventable cause of death especially among PLHIV.…”
mentioning
confidence: 99%
See 1 more Smart Citation